Philosophical perspectives for pragmatics - Sbisà, Marina; Östman, Jan-Ola; Verschueren, Jef (Handbook of pragmatics highlights, 2011)
The ten volumes of Handbook of Pragmatics Highlights focus on the most salient topics in the field of pragmatics, thus dividing its wide interdisciplinary spectrum in a transparent and manageable way. While the other volumes select specific cognitive, grammatical, social, cultural, variational, interactional, or discursive angles, this 10th volume focuses on the interface between pragmatics and philosophy and reviews the philosophical background from which pragmatics has taken inspiration and with which it is constantly confronted. It provides the reader with information about authors relevant.